Conceptual Understanding and Mathematical Representation Analysis of Realistic Mathematics Education Based on Personality Types - Kowiyah, Kowiyah; Mulyawati, Ima; Umam, Khoerul (Universitas Islam Raden Intan Lampung, INDONESIA, 2019)
Conceptual understanding and representation in mathematics are both important mathematical abilities to develop. Conceptual understanding and representation abilities are needed by students to solve mathematical problems. The aim of this research was to describe the representation of mathematics of RME based on student's personality type, the conceptual understanding in RME based on student's personality type. In this research, 8 PGSD students from artisan, idealist, guardian, and rational personality types were selected as subjects. The methods used in this research were tests, interviews, and documentation of personality type questionnaires of the students according to (Keirsey, 1984)). The tests and interviews were analyzed to describe the conceptual understanding and representation abilities of the students. The results of this research were that the students with the rational personality type were very good at identifying and making examples, traits and conditions. Students with the idealist personality type were very good at identifying verbally and in written form. All four personality types’ conceptual understanding when identifying and distinguishing concepts was still poor. Meanwhile, for the mathematical representation aspect, all four personality types were very good at visual mathematical representation in the form of figures and tables.